Influences of Curing Period and Sulfate Concentration on the Dynamic Properties and Energy Absorption Characteristics of Cement Soil - Jing-Shuang Zhang (MDPI AG, 2021)
To study the influences of curing period and sulfate concentration on the dynamic mechanical properties of cement soil, this study used a split Hopkinson pressure bar device. Impact tests were conducted on cement soil specimens with different curing periods and different sulfate concentrations. The relationships between the dynamic stress–strain, dynamic compressive strength, and absorption energy of these cement soil specimens were analyzed. The test results show that with continuous loading, cement soil specimens mainly experience an elastic stage, plastic stage, and failure stage; with increasing curing period and sulfate concentration, the dynamic compressive strength and absorption energy of cement soil specimens follow a trend of first increasing and then decreasing. The dynamic compressive strength and absorption energy of cement soil specimens reached maximum values at a curing period of 14 d and a Na2SO4 solution concentration of 9.0 g/L. Increasing the dynamic compressive strength and absorption energy can effectively improve the ability of cement soil specimens to resist damage. This paper provides a practical reference for the application of cement soil in dynamic environments.